Construction of restorative justice regulations in the integrated justice system - Prayogo Laksono,; Made Warka,; Frans Simangungsong, (Technium Social Sciences Journal, 2026)
The Republic of Indonesia is a constitutional state (rechtsstaat), which means that all attitudes, behaviors, and actions, whether carried out by the authorities or by its citizens, must be based on the law. Indonesia as a constitutional state is affirmed in Article 1 paragraph (3) of the 1945 Constitution of the Republic of Indonesia. Basically, a constitutional state aims primarily to provide legal protection for the people. Philipus M Hadjon states that legal protection for the people against government actions is based on two principles, namely the principle of human rights and the principle of the constitutional state. This research uses a normative juridical research type. The construction of restorative justice arrangements in the integrated criminal justice system is necessary because all criminal cases resolved under the Criminal Code and Criminal Procedure Code must be resolved through the integrated criminal justice system via law enforcement officials so that dispute resolutions involving the community, which are recognized and developed within the community, do not receive facilities under the old Criminal Code and Criminal Procedure Code, even though the application of restorative justice provisions in the Criminal Code has been included in the provisions of Article 54 of Law Number 1 of 2023 concerning the Criminal Code.The application of restorative justice provisions in the Criminal Code is stipulated in Article 54 of Law Number 1 of 2023 concerning the Criminal Code Criminal Law Code, the provisions still have weaknesses in that there is no specific law regulating the restorative justice mechanism, so that the resolution of cases through this approach does not yet have a strong legal basis, which can lead to legal uncertainty.